Cure-induced strain and failure in deltoid of composite T-joints. (February 2021) - Hisada, Shinsaku; Minakuchi, Shu; Takeda, Nobuo
Abstract: Composite structures are generally considered to be difficult to apply to joining components. A T-joint is an important element in aircraft structures that transfers loads between vertical and horizontal panels. However, T-joints present cracks that occur in the deltoid during their manufacture because of process-induced cure and thermal stress. Such cracking significantly reduces the mechanical performance of T-joints. Although a number of studies have been conducted on the behavior of T-joints under mechanical loading, studies on the behavior of T-joints during curing are limited. Therefore, this study is proposed to be the first to measure the strain distribution throughout the deltoid using an optical fiber. Firstly, three types of deltoid structures with differently oriented interlaminar toughened layers were used, and the relationship between the strain distribution and the failure pattern of the deltoid were examined. Based on the experimental results, finite element analysis is conducted and a failure index for the process-induced failure of deltoids was developed. Finally, a deltoid configuration to suppress process-induced failure was established and validated based on the results of the experiment and analysis.